Effect of reactive power loading on the stability of power network bus voltage and transmission line - Goa Tella, Teshome; Simiyu Sitati, Stanley; Nyauma Nyakoe, George (International Journal of Engineering and Technology, 2018)
Increased loading results in the instability of bus voltages and power transmission lines, which results in the outage of power transmission lines. For stable operation, finding the maximum loading limit of buses is needed. This paper introduces newly proposed modified voltage stability index (MVSI) and line stability index (Lst) that are used to rank buses and lines, respectively, based onÂ the severity of load contingency. Thus, to account for the effect of inductive load on bus voltage and line stability, only load reactive powerÂ is increased upÂ to itsÂ maximumÂ stability limit. The MVSI and Lst areÂ determinedÂ using NewtonÂ RaphsonÂ power flow. Buses and linesÂ are then ranked using MVSI and LstÂ based on the severity of bus loading. The effectiveness of the new stability indices is evaluated against conventional stability indices based on the IEEE-14 bus standard systems and tested on the Ethiopian 230 KV power network. Results show that the proposed indices perform better in ranking buses and lines. Â Â Â